Multidimensional quantification of uncertainty and application to a turbulent mixing model. (11th May 2017) - Barmparousis, Christos; Drikakis, Dimitris
Summary: This paper concerns the implementation of the generalized polynomial chaos (gPC) approach for parametric studies, including the quantification of uncertainty (UQ), of turbulence modelling. The method is applied to Richtmyer‐Meshkov turbulent mixing. The K − L turbulence model has been chosen as a prototypical example, and parametric studies have been performed to examine the effects of closure coefficients and initial conditions on the flow results. It is shown that the proposed method can be used to obtain a relation between the uncertain inputs and the monitored flow quantities, thus efficiently performing parametric studies. It allows the simultaneous calibration and quantification of uncertainty in an efficient numerical framework. Abstract : It is shown that the proposed method can be used to obtain a relation between the uncertain inputs and the monitored flow quantities, thus performing parametric studies in an integrated manner. It allows the simultaneous calibration and quantification of uncertainty in an efficient numerical framework. The framework has been successfully applied in the quantification of the uncertainty due to the closure assumptions of a two equation model in a compressible turbulent mixing case.